SEVERE INSULIN RESISTANCE REQUIRING HIGH DOSE INSULIN IMPROVED WITH ADD-ON EMPAGLIFOZIN THERAPY: A CASE REPORT - Ooi, Xin Yi; See, Chee Keong; Arifin, Noorhidayah (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Empagliflozin, an SGLT-2 transporter inhibitor is known to improve glucose control with weight loss. Its role in reducing insulin resistance is under-recognised. CASE A young patient with BMI of 47.4 kg/m2 and diabetes has been treated with high dose multiple daily insulin injection totalling 600 iu/day (4.2 iu/kg/day). Despite compliance, lifestyle intervention and add-on therapy of metformin and vildagliptin, insulin requirement only reduced to 275 iu/day(2 iu/kg/day) and remained static. We subsequently started him on 25 mg daily of empaglifozin. CONCLUSION In an obese patient with insulin resistance, empaglifozin improved insulin sensitivity leading to significant reduction in insulin requirement